O segundo grau profissionalizante na grande São Paulo de acordo com a lei 5692/71 (1972-1982) - Turoni, Ravy de San Juan Abreu (2019)
The purpose of this research is to analyze the implementation and dissemination of secondary vocational schools in the State of São Paulo, in accordance to law 5692/71, in force from 1972 to 1982, the duration of obligatory secondary vocational education. For this purpose, official documents were analyzed, such as law 5692/71, Reports, Referrals, Deliberations and Resolutions of the Federal Council and the State Board of Education, contributing to the knowledge regarding the formulation and standardization of the secondary education reform, as well as for the understanding of what the authorities that envisioned and created guidelines for the implementation of the reform understood as "vocational education" for this level of education. To analyze the dissemination of this reform throughout the State of São Paulo, a list of the professional qualifications offered by public and private schools was examined, edited in 1981 by the Education Information Center, linked to the Department of Education in Brazil. This document was obtained from the Public Archive of the State of São Paulo. It is hypothesized that educational institutions that were not vocational schools before law 5692/71 was passed, had to adapt the school organization to offer these courses. To examine how this process occurred, an analysis of the 1978 School Plan of E.E. Dr. Carlos Augusto Villalva Jr., a public school located in the city of São Paulo, in the neighborhood of Jabaquara, is carried out. Through this record, it was possible to analyze the Special Part of the curriculum, what professional courses were offered, what subjects were taught and how these courses were organized in that institution